The Value of Desmethylclozapine and Serum CRP in Clozapine Toxicity: A Case Report - Khalid Abou Farha; Andre van Vliet; Henderikus Knegtering; Richard Bruggeman (Case Reports in Psychiatry)
Clozapine, an atypical antipsychotic, has proved to be superior to other antipsychotics in treating patients with refractory schizophrenia. An increased plasma clozapine level above the therapeutic window may be associated with serious adverse events including paralytic ileus. Clozapine toxicity may occur in association with infection or after drug overdose. In a medical emergency situation, differentiating between a toxic clozapine ingestion and an infection-induced toxicity might be hindered by associated CNS changes and by the clozapine modulation of the inflammatory process. This may delay prompt initiation of a tailored treatment strategy. Here, we report a case of paralytic ileus developed within the context of clozapine toxicity. Although the underlying cause of toxicity was not clinically obvious, giving antimicrobial therapy resulted in an improvement in the patient’s clinical condition. This report indicates the value of serum levels of C-reactive protein and desmethylclozapine, major metabolite of clozapine, in the treatment of aetiologically unclear clozapine toxicity.